Desain dan Uji Coba Media Pembelajaran Berbasis Videoscribe Sebagai Sumber Belajar Pada Materi Bentuk Molekul Kelas X IPA SMA - Astari Shakina; Neti Afrianis (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
This research was instigated by the importance of technology-based learning facilities for students in learning Chemistry. This research aimed at knowing validity and practicality levels of the media designed. It was conducted to the tenth-grade students of MIA 2 of State Senior High School 1 Pekanbaru in the Academic Year of 2019/2020, and they were 12 students.It was Research and Development (R&D) with Borg and Gall modification model. The subjects of this research were who tested the validity (the experts of media and material) and practicality (teachers and students). Interview and questionnaire were used to collect the data. The final product was in the form of a valid learning media. Videoscribe-based learning media on Molecular Shapes lesson developed was tested valid by the experts of media and material with 91.87% mean percentage (very valid) and it was tested practical by 2 Chemistry subject teachers and 12 students with 91.02% mean percentage. Based on these findings, it could be concluded that Videoscribe-based learning media on Molecular Shapes lesson was valid and practical, sothe testcould be done at thefurther stage.